The Role of Market Forces in Assuring Contractual Performance - Klein, Benjamin; Leffler, Keith B. (Journal of Political Economy, 1981)
The conditions under which transactors can use the market (repeat-purchase) mechanism of contract enforcement are examined. Increased price is shown to be a means of assuring contractual performance. A necessary and sufficient condition for performance is the existence of price sufficiently above salvageable production costs so that the nonperforming firm loses a discounted steam of rents on future sales which is greater than the wealth increase from nonperformance. This will generally imply a market price greater than the perfectly competitive price and rationalize investments in firm-specific assets. Advertising investments thereby become a positive indicator of likely performance.